2023
DOI: 10.3390/cancers15092493
|View full text |Cite
|
Sign up to set email alerts
|

Supratotal Surgical Resection for Low-Grade Glioma: A Systematic Review

Abstract: Low-grade gliomas (LGGs) are optimally treated with up-front maximal safe surgical resection, typically defined as maximizing the extent of tumor resection while minimizing neurologic risks of surgery. Supratotal resection of LGG may improve outcomes beyond gross total resection by removing tumor cells invading beyond the tumor border as defined on MRI. However, the evidence regarding supratotal resection of LGG, in terms of impact on clinical outcomes, such as overall survival and neurologic morbidities, rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Favorable outcomes, including recurrence and survival, of supramaximal resection were also reported for low-grade gliomas ( 91 ). More broadly, reviews for low-grade gliomas and for glioblastoma suggested that supramaximal resection was effective and safe ( 88 , 92 ). Further and larger clinical studies are needed for more robust evidence.…”
Section: Treating Gliomamentioning
confidence: 99%
“…Favorable outcomes, including recurrence and survival, of supramaximal resection were also reported for low-grade gliomas ( 91 ). More broadly, reviews for low-grade gliomas and for glioblastoma suggested that supramaximal resection was effective and safe ( 88 , 92 ). Further and larger clinical studies are needed for more robust evidence.…”
Section: Treating Gliomamentioning
confidence: 99%